Psychological Impact after COVID-19 Infection among Bangladeshi Ex-patriot working in Kuwait Armed Forces: A Cross-sectional Study - Rahman, Ashiqur; Haider, Rina; Tasnim, Nazifa; Sharmin, Faria; Chowdhury, Imru Al Quais (Journal of Armed Forces Medical College, Bangladesh, 2024)
Background: The Covid-19 pandemic had a huge impact on the mental health and caused strong psychological stress with depression to the people. After recovery from COVID-19, many patients were prone to develop emotional distress and even disaster mental health which might have relation with this disease. Objective: To assess the psychological impact (depression) after covid-19 amongst the Bangladeshi personnel in Kuwait. Methods: This cross sectional study was carried out among Bangladeshi military persons working in Kuwait Armed Forces from July 2021 to June 2022. Total 108 persons were randomly selected, who have suffered in Covid-19. Data were collected by structured questionnaires and analyzed by SPSS v21. Results: The respondents’ mean (±SD) age is 37.75 (±5.48) years; ranged from 30 to 51 years. The CSE depression scale, the scores (sum of the 20 questions) range is 11-25. The mean score in 14.40±2.96. The difference of Depression Scale in relation to staying with family were significant by t test. In case of financial loss due to Covid-19, significant association was found with Depression Scale score. There was positive correlation between Depression Scale with Days of sufferings. Post-covid complications had statistically significant difference with poor appetite, feeling of fear and disturbance of sleep. Health condition had significant positive correlations with feeling of fear and sadness. As score of 16 points or more is considered depressed, so 29(16.9%) persons are found to be depressed. Conclusion: This study focused on the psychological status, especially depression of recovered COVID-19-infected patients. These findings inform the necessity of psychological interventions that will reduce psychological impact and depression during the epidemic. Health care providers will have important role to address these emotional outcomes as part of the pandemic response. JAFMC Bangladesh, Vol 20, No 1 (June) 2024:14-17